Aplikasi Kuartu Berbasis Android Sebagai Media Pertukaran Informasi Kartu Nama - Nandi Syukri; Eko Budi Setiawan (Ultimatics : Jurnal Teknik Informatika, 2017)
Business Card is the most efficient, effective and appropriate tool for every business men no matter they are owners, employees, more over marketers to provide information about their businesses. Unfortunately, it is very difficult to bring and manage business card in large numbers also to remember the face of the business card owner. A Business Card application need to be built to solve all those issues mentioned above. The Application or software must be run in media which can be accessed anywhere and anytime such as smart phone. Kuartu is as business card application run in mobile devices. Kuartu is developed using object base modeling for mobile sub system. The platform of the mobile sub system is android, as it is the most widely used platform in the world. The Kuartu application utilizing NFC and QR Code technology to support the business card information exchange and the Chatting feature for communication. Based on the experiment and test using black box methodology, it can be concluded that Kuartu application makes business card owner to communicate each other easily, business card always carried, easy to manage the cards and information of the business card owner can be easily obtained. Index Terms— Business Card, Android, Kuartu, NFC, QrCode, Chatting.